Outcomes of intravesical Bacillus Calmette-Guerin in patients with non-muscle invasive bladder cancer: a retrospective study in Australia - Pillippu Hewa, Chamodi; Della-Fiorentina, Stephen; Haghighi, Kayvan; Chua, Wei; Kok, Peey-Sei (Frontiers in Urology, 2024)
Induction intravesical Bacillus Calmette-Guerin (BCG) followed by maintenance after transurethral resection of bladder tumor, is the standard adjuvant therapy for high-risk non-muscle invasive bladder cancer (NMIBC). There is sparse evidence on the practice of intravesical BCG in Australia.Our aim was to determine the outcomes of intravesical BCG therapy in NMIBC in Southwestern Sydney.This was a multi-center retrospective audit of NMIBC patients who received intravesical BCG between January 2008 and June 2020. Data was collected across six tertiary hospitals in South Western Sydney. Primary outcome was disease-free survival (DFS). Secondary outcomes were overall survival (OS), BCG induction and maintenance rates.Of the 200 eligible patients over 12.5 years, median age was 77 years and 83% were male. Of these, 55%, 4.5%, 35% and 5% were Tis, Ta, T1 and unknown stage, respectively. All patients received induction BCG and 56% received maintenance BCG (range 3-36 months). Completion rate of induction BCG was 91%. Only 9% ceased treatment due to intolerance. The median duration of cystoscopy follow-up was 17 months. After a median follow-up time of 37 months, 55% developed recurrence (29% non-muscle invasive, 32% muscle-invasive disease, 8% distant metastasis). The 1year and 5-year DFS rates were 72% and 41% (median DFS: 39 months). The 1-year and 5-year OS rates were 98% and 87% (median OS: not reached).The DFS and OS rates were comparable to previous literature. This provides real-world data to assist future clinical trials in NMIBC.